(untitled) (Global Journal of Human-Social Science, 2021)
One of the main objections often advanced against the use of indigenous languages in the domain of Information and Communication Technology (Henceforth, ICTS) is the alleged absence of relevant terminology comparable to that available in exoglossic languages. This erroneous belief is often expressed as local languages cannot adequately express technological and scientific concepts. With increasing numbers of computers and penetration of the internet in different localities in Cameroon, some linguists are creating and standardizing ICTS terminology in different languages. Due to the scarcity and significant absence of most Cameroonian languages in cyberspace, this study examines the strategies used in creating some ICTS terms in the Kom language. The study advances some reasons for the digital divide in Cameroon and also looks at the importance of developing ICTS. It examines some challenges and principles of terminology creation in Kom. Based on data collected through a translation of a 45-word list on some parts of a computer from English to Kom, the study uses the International Organization for Standardization (ISO) is a framework that guides the creation of terms in different languages by Sager (1990:89).